2014
DOI: 10.1371/journal.pone.0108854
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics in Human Pulmonary Tuberculosis Disease: A Pilot Study

Abstract: We aimed to characterize metabolites during tuberculosis (TB) disease and identify new pathophysiologic pathways involved in infection as well as biomarkers of TB onset, progression and resolution. Such data may inform development of new anti-tuberculosis drugs. Plasma samples from adults with newly diagnosed pulmonary TB disease and their matched, asymptomatic, sputum culture-negative household contacts were analyzed using liquid chromatography high-resolution mass spectrometry (LC-MS) to identify metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 63 publications
4
111
0
Order By: Relevance
“…These metabolites could be classified in various groups probably related to specific diet, environmental chemicals, and household microbes. This study showed eight metabolites that were specifically up-regulated by the mycobacterial infection, such as glutamate, choline derivatives, M. tuberculosis cell wall glycolipids, and lipid mediators of inflammation (47).…”
Section: Metabolomics and Diagnostic Biomarkersmentioning
confidence: 83%
“…These metabolites could be classified in various groups probably related to specific diet, environmental chemicals, and household microbes. This study showed eight metabolites that were specifically up-regulated by the mycobacterial infection, such as glutamate, choline derivatives, M. tuberculosis cell wall glycolipids, and lipid mediators of inflammation (47).…”
Section: Metabolomics and Diagnostic Biomarkersmentioning
confidence: 83%
“…14,15,22,23 For analysis, samples were batch randomized into 20-sample batches, with each batch containing an equal number of cases and controls in random order. Pooled reference plasma was run prior to and after each batch for quality control and quality assurance.…”
Section: Metabolomic Analysismentioning
confidence: 99%
“…Plasma sample aliquots (65 lL) were treated with 130 lL acetonitrile (2:1 vol/vol) containing an internal isotopic standard mix (3.5 lL per sample) as previously described. 15,23 The internal standard mix for quality control (Supplementary Table S1) consisted of 14 stable isotopic chemicals covering a broad range of chemical properties represented in small molecules. 15 Samples were mixed and placed on ice for 30 minutes prior to centrifugation for 10 minutes (16,100g at 48C) to remove protein.…”
Section: Metabolomic Analysismentioning
confidence: 99%
“…We also recently identified extracellular metabolites specific to M. tuberculosis (25), supporting the potential of metabolomics in exploring novel biomarkers to better understand its biology and pathogenesis. On the other hand, metabolomics applied on direct patient samples may reveal specific diagnostic markers or be used to monitor treatment response (26)(27)(28)(29). It has been shown that volatile organic compounds (VOCs) in the urine of TB patients can be distinguished from those of healthy subjects (26).…”
mentioning
confidence: 99%
“…A study using nuclear magnetic resonance spectroscopy-based metabolomics on serum samples from TB patients demonstrated discrimination between patients and healthy controls (27). In another metabolomics study, several abundant metabolites were identified, including two mycobacterium-derived cell wall glycolipids, in EDTA-plasma from TB patients that were not identified in household contacts (28). However, patients with other bacterial infections were not included as controls in these studies, and thus, the potential of such a metabolic profile for use in the diagnosis of TB remains to be determined.…”
mentioning
confidence: 99%